Adenosine Deaminase Deficiency – More Than Just an Immunodeficiency - Whitmore, Kathryn V.; Gaspar, Hubert B. (Frontiers in Immunology, 2016)
Adenosine deaminase (ADA) deficiency is best known as a form of severe combined immunodeficiency (SCID) which results from mutations in the gene encoding adenosine deaminase. Affected patients present with clinical and immunological manifestations typical of a severe combined immunodeficiency. Therapies are currently available that can that target these immunological disturbances and treated patients show varying degrees of clinical improvement. However, there is now a growing body of evidence that deficiency of ADA has significant impact on non-immunological organ systems. This review will outline the impact of ADA deficiency on various organ systems, starting with the well understood immunological abnormalities. We will discuss possible pathogenic mechanisms and also highlight ways in which current treatments could be improved. In doing so, we aim to present ADA deficiency as more than an immunodeficiency and suggest that it should be recognized as a systemic metabolic disorder that affects multiple organ systems. Only by fully understanding ADA deficiency and its manifestations in all organ systems can we aim to deliver therapies that will correct all the clinical consequences.